2012
DOI: 10.1016/j.biopsych.2011.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Rare Copy Number Variants in Tourette Syndrome Disrupt Genes in Histaminergic Pathways and Overlap with Autism

Abstract: Background Studies of copy number variation (CNV) have successfully characterized loci and molecular pathways involved in a range of neuropsychiatric conditions. We conducted an analysis of rare CNVs in Tourette Syndrome (TS) to identify novel risk regions and relevant molecular pathways, evaluate the burden of structural variation in cases versus controls, and to assess the overlap of identified variations with those implicated in other neuropsychiatric syndromes. Methods We conducted a case-control study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 79 publications
(92 reference statements)
10
163
2
1
Order By: Relevance
“…The presence of specific psychiatric comorbidities in some male members of this pedigree could also be explained by a dysfunction in the histaminergic system, as overriding inhibition of competing pathways within parallel cortico-striato-thalamo-cortical loops can hinder behavioral switching as seen in obsessivecompulsive disorder [89]. A more general association of histaminergic pathways with TS was identified by analysis of rare CNVs in a subsequent study [77]. The hypothesis of an involvement of the histaminergic system in the pathogenesis of TS was also supported by a more recent report on single nucleotide polymorphisms in the HDC region that are associated with TS [78].…”
Section: Promising Avenues For Researchmentioning
confidence: 89%
See 1 more Smart Citation
“…The presence of specific psychiatric comorbidities in some male members of this pedigree could also be explained by a dysfunction in the histaminergic system, as overriding inhibition of competing pathways within parallel cortico-striato-thalamo-cortical loops can hinder behavioral switching as seen in obsessivecompulsive disorder [89]. A more general association of histaminergic pathways with TS was identified by analysis of rare CNVs in a subsequent study [77]. The hypothesis of an involvement of the histaminergic system in the pathogenesis of TS was also supported by a more recent report on single nucleotide polymorphisms in the HDC region that are associated with TS [78].…”
Section: Promising Avenues For Researchmentioning
confidence: 89%
“…In 2012, a case-control study of 460 patients with TS focused on copy number variants (CNVs) to identify risk regions or molecular pathways which may be associated with TS [77]. The authors found no statistically significant increase in CNVs when comparing patients with TS to controls, however there was some overlap between CNVs found in patients with TS and those previously identified in autism spectrum disorder.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Studies of adults with schizophrenia and epilepsy demonstrate lower diagnostic yields of ~5% [11,12,18,23,24]. For other neurodevelopmental conditions there is either conflicting evidence for increased CNV burden, such as for bipolar disorder [25,26], or no evidence, as for Tourette's syndrome and dyslexia [19,20,27]. In all cases burden statistics are more significant when considering de novo events exclusively [15,18,21,22,26].…”
Section: Copy Number Variation In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Linkage studies have identified candidate autism susceptibility genes at multiple loci, most consistently on chromosomes 7q, 15q, and 16p (Autism Genome Project Consortium et al 2007;Sakurai et al 2011). Exome sequencing in sporadic cases of autism has detected new mutations (O'Roak et al 2011), and copy number variant studies have identified several hundred copy number variants putatively linked to autism (Fernandez et al 2012). The candidate genes most strongly implicated in NDD causation encode for proteins involved in synaptic architecture, neuro transmitter synthesis (e.g., g-amino butyric acid serotonin), oxytocin receptors, and cation trafficking (Sakurai et al 2011).…”
Section: Perspectives | Editorialmentioning
confidence: 99%